Genetic diversity of cultivated accessions and wild species of rubber tree using EST‑SSR markers - Perseguini, Juliana Morini Küpper Cardoso; Romão, Lineu Roberto de Castro; Briñez, Boris; Scaloppi Junior, Erivaldo José; Gonçalves, Paulo de Souza; Benchimol, Luciana Lasry (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the efficiency of EST‑SSR markers in the assessment of the genetic diversity of rubber tree genotypes (Hevea brasiliensis) and to verify the transferability of these markers for wild species of Hevea. Forty‑five rubber tree accessions from the Instituto Agronômico (Campinas, SP, Brazil) and six wild species were used. Information provided by modified Roger’s genetic distance were used to analyze EST‑SSR data. UPGMA clustering divided the samples into two major groups with high genetic differentiation, while the software Structure distributed the 51 clones into eight groups. A parallel could be established between both clustering analyses. The 30 polymorphic EST‑SSRs showed from two to ten alleles and were efficient in amplifying the six wild species. Functional EST‑SSR microsatellites are efficient in evaluating the genetic diversity among rubber tree clones and can be used to translate the genetic differences among cultivars and to fingerprint closely related materials. The accessions from the Instituto Agronômico show high genetic diversity. The EST‑SSR markers, developed from Hevea brasiliensis, show transferability and are able to amplify other species of Hevea.